Public Fund Misappropriation and Fiscal Non-Compliance: Tax and Zakat Evidence from Indonesia - Fathin Azzahra; Rina Desiana; Ella Annissa; Rizki Mulia Nanda (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
Public fund misappropriation poses a systemic threat that not only drains state finances but also erodes public trust in both conventional and Islamic fiscal institutions. This study aims to descriptively and qualitatively analyze the impact of corruption and public fund misappropriation—particularly of tax and zakat funds—on taxpayer compliance, muzakki compliance, and Indonesia’s economic growth, with enhanced analysis from an Islamic economic perspective grounded in maq??id al-shar??ah. Using secondary data from Indonesia Corruption Watch (ICW), Transparency International, the Directorate General of Taxes (DJP), and BAZNAS for the 2010–2024 period, the findings reveal four main conclusions: (1) potential state losses from corruption—as recorded by ICW—escalated from IDR 3.7 trillion (2010) to IDR 279.9 trillion (2024); (2) cases of tax and zakat fund misappropriation significantly weaken tax morale and muzakki compliance; (3) zakat misappropriation violates all dimensions of maq??id al-shar??ah, from ?if? al-m?l to ?if? al-nasl; and (4) institutional reforms grounded in transparency, digitalization, and Islamic fiscal synergy are key instruments for restoring public trust. The study implies the need for synergy between tax reform, zakat governance, and consistent law enforcement as a holistic strategy for equitable and sustainable economic growth.